2022
DOI: 10.1055/a-1783-4802
|View full text |Cite
|
Sign up to set email alerts
|

The performance and safety of motorized spiral enteroscopy, including in patients with surgically altered gastrointestinal anatomy: a multicenter prospective study

Abstract: BACKGROUND AND STUDY AIMS: Data are scarce on the efficacy and safety of the Motorized spiral enteroscopy (MSE). No data are available on the utility of this technique in patients with surgically-altered gastrointestinal (GI) anatomy. We aimed to evaluate the safety and efficacy of MSE in patients with suspected small-bowel disease including those with surgically-altered GI anatomy. METHODS: A multicenter prospective observational, uncontrolled study evaluated MSE in consecutive patients with suspected small-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 28 publications
2
34
0
3
Order By: Relevance
“…The available studies therefore do not report an increased rate of AEs 17 18 19 20 ; however, there is potential concern about an increased rate of AEs using the motorized technique. Recently, a study found no increase in the AE rate for MSE in patients who had undergone previous surgery 21 . In the current study, 21.5 % of the patients had previous abdominal surgery, with 10 % having surgically altered GI anatomy (40.8 % and 19.2 % of the CP2 group, respectively).…”
Section: Discussionmentioning
confidence: 98%
“…The available studies therefore do not report an increased rate of AEs 17 18 19 20 ; however, there is potential concern about an increased rate of AEs using the motorized technique. Recently, a study found no increase in the AE rate for MSE in patients who had undergone previous surgery 21 . In the current study, 21.5 % of the patients had previous abdominal surgery, with 10 % having surgically altered GI anatomy (40.8 % and 19.2 % of the CP2 group, respectively).…”
Section: Discussionmentioning
confidence: 98%
“…One study reported mild cardiopulmonary AEs related to general anesthesia in 3/132 patients (2.3 %) 1 ; in their series, Beyna et al reported two SAEs related to sedation/anesthesia 8 . Interestingly, Al-Toma et al performed 92 % of MSEs in their study with only propofol sedation, with no adverse events related to sedation reported 3 . Although the choice of sedation is usually governed by procedure complexity, clinical factors, and local organizational protocols 5 , future studies will have to clarify which is the most appropriate and safest sedation for antegrade MSE.…”
mentioning
confidence: 92%
“…Conversely, MSE safety data are still scarce. The evidence on the safety of MSE in unselected populations is still based on a limited number of patients, approximately 750 from seven studies to date 1 2 3 4 6 7 8 . For MSE, minor adverse events (AEs), such as superficial mucosal tears, submucosal hematomas, and throat discomfort, are to be expected in about a quarter of patients 1 2 3 4 6 7 .…”
mentioning
confidence: 99%
“…Although Akerman et al first reported on the concept of motorized spiral enteroscopy (MSE) over a decade ago 1 , it has only recently been introduced into actual clinical practice 2 and our understanding of its safety and performance is still being fine-tuned. In this issue of Endoscopy , Al-Toma et al, from the Netherlands, report on their multicenter prospective uncontrolled study in a “real-world” setting, with a focus on performance and safety in “all-comers,” including patients with a previous history of surgery and altered anatomy 3 . Their study included 170 patients, with a median age of 64 years.…”
mentioning
confidence: 99%
“…Another crucial and important point that should be borne in mind, which is specific to antegrade MSE, relates to the interaction of the raised spiral-moiety with the patient’s upper esophageal sphincter and esophagus. In their series, Al-Toma et al 3 elected not to predilate the upper esophageal sphincter with a bougie (as previously described 2 4 ), but alternatively avoided esophageal injury by aborting procedures where excessive resistance was encountered on insertion through the upper esophageal sphincter (n = 2). However, deep esophageal laceration (Buscaglia 4) from impaction of the spiral overtube in the upper esophagus on withdrawal (despite no resistance on insertion) has also been reported 8 , and clinicians should be alerted to this potential risk.…”
mentioning
confidence: 99%